2017
DOI: 10.1891/1933-3196.11.4.195
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Flash Technique in EMDR Therapy: Four Case Examples

Abstract: This article introduces the flash technique, a new technique used during the preparation phase of eye movement desensitization and reprocessing (EMDR) therapy to facilitate processing of intense, traumatic memories that clients might otherwise be resistant to access. Anecdotal evidence suggests that this technique may make it possible for clients to access these memories initially in a minimally disturbing way, reducing their emotional intensity so that they can then be more easily and fully processed using EM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 22 publications
5
40
1
Order By: Relevance
“…However, in the case of severe trauma, clients may find the memory too traumatic and may go into an abreaction such as dissociation. In 2017, Manfield et al (2017) developed the FT to help clients bring down their distress level quickly so that EMDR can proceed. In the FT, circa 2017, clients only need to identify the memory to be processed and then focus on a positive experience.…”
Section: The Flash Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…However, in the case of severe trauma, clients may find the memory too traumatic and may go into an abreaction such as dissociation. In 2017, Manfield et al (2017) developed the FT to help clients bring down their distress level quickly so that EMDR can proceed. In the FT, circa 2017, clients only need to identify the memory to be processed and then focus on a positive experience.…”
Section: The Flash Techniquementioning
confidence: 99%
“…There are various speculations regarding the putative mechanism for the observed rapid effects. Manfield (2017) suggested that FT might be similar to subliminal messaging, with the client accessing the memory so briefly that he or she was not consciously aware of the details of the memory to be processed. However, it is not clear how the current practice of FT, with the blinking, can be related to subliminal messaging.…”
Section: Concepts From Neuroscience and Working Memory Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to keep in mind that the application of CIPOS does lead to complete memory reprocessing with the majority of cases. Recently the Flash Technique (Manfield et al, 2017) was introduced. It shows some similarities but needs further research and evaluation regarding the position in EMDR Therapy.…”
Section: The Fourth Level: the Proceduresmentioning
confidence: 99%
“…The rationale behind including values clarification was to help clients evaluate what was important and to promote behavioural change. • Dissociation, hyperarousal and resistance to visiting the trauma memory were also managed by using the flash technique borrowed from EMDR as described by Manfield et al (2017). Using this technique allowed brief exposure of a few seconds to the trauma memory in order to safely prime the clients for full engagement with the trauma memory.…”
Section: Case Formulation and Designmentioning
confidence: 99%